Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12864-022-08657-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome study digs out BMP2 involved in adipogenesis in sheep tails

Abstract: Background Hu sheep and Tibetan sheep in China are characterized by fat tails and thin tails, respectively. Several transcriptomes have been conducted in different sheep breeds to identify the differentially expressed genes (DEGs) underlying this trait. However, these studies identified different DEGs in different sheep breeds. Results Hence, RNA sequencing was performed on Hu sheep and Tibetan sheep. We obtained a total of 45.57 and 43.82 million … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…For example, candidate genes PDGFD, BMP2, TBXT, and HOXB13 were detected by selective sweep or GWAS analysis 15,[18][19][20][21][22] , which are involved in preadipocyte differentiation and associated with fat deposition in sheep 5,23 . In addition, many candidate genes, microRNA and lncRNA were identified by transcriptomic and proteomic approaches, such as PGDFD, BMP2, IL6, ADIPOQ, miR-432, most of which are related to fat deposition and lipid metabolism [24][25][26][27][28] . Those studies revealed plenty of candidate genes and regulatory elements associated with the fat tail phenotype and suggested a complex genetic mechanism for the fat tail phenotype.…”
mentioning
confidence: 99%
“…For example, candidate genes PDGFD, BMP2, TBXT, and HOXB13 were detected by selective sweep or GWAS analysis 15,[18][19][20][21][22] , which are involved in preadipocyte differentiation and associated with fat deposition in sheep 5,23 . In addition, many candidate genes, microRNA and lncRNA were identified by transcriptomic and proteomic approaches, such as PGDFD, BMP2, IL6, ADIPOQ, miR-432, most of which are related to fat deposition and lipid metabolism [24][25][26][27][28] . Those studies revealed plenty of candidate genes and regulatory elements associated with the fat tail phenotype and suggested a complex genetic mechanism for the fat tail phenotype.…”
mentioning
confidence: 99%
“…Moreover, an increased VEGFA expression was considered as one means of genetic adaptation to hypoxia at high altitudes (Edea et al, 2019; Zhang et al, 2016). Also, the closest gene located at 350 kb downstream from the most significant marker on OAR13 at 48.91 Mbp was the BMP2 gene located at ~48.46–48.47 Mbp, which is involved in the regulation of adipogenesis metabolism (Jin et al, 2022) and was found to be a potential gene for fat tail deposition in Barbarine sheep (Baazaoui et al, 2021). Other genomic regions detected probably reflect other selection differences between the breeds used in this study as we used only one fat‐tailed breed.…”
Section: Discussionmentioning
confidence: 99%
“…Ppargc1a plays a pivotal role in lipid and metabolic regulation in many vital organs, including adipose tissue, skeletal muscle, heart, liver, and kidney 58 . Bmp2 is likely to induce adipogenesis by promoting the expression of lipoxygenase (LOX) and PPAR gamma (PPARγ) in preadipocytes 59 . Yang et al 60 reported that Pik3r3 regulates PPAR alpha (PPARα) expression to stimulate fatty acid β-oxidation.…”
Section: Discussionmentioning
confidence: 99%